Cardini, Franco - Del Nero, Domenico. La crociatta dei fanciulli. Firenze: Giunti. 1999, 171 pp - Hubeñak, Florencio (2002)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina